Influence of customer orientation and internal marketing on job satisfaction among employees in banking industry in Lagos, Nigeria - Obodoechi, Acho Kenneth (2020)
The competitive nature and environment that banking industry operates has been the cardinal factor which has compelled them to focus their strength towards breeding customer-oriented employees through the engagement of internal marketing practice that will metamorphose to the employees’ job satisfaction in Nigeria banking industry. Banking industry is considered as one of the most important financial industry globally. It is thought to be the only reliable economic institution through which the economics of a nation can be ascertained. Moreover, banking industry in Nigeria has got a pivotal role to play in order to establish decent economic relationship that will enhance them the capability to compete globally and become one of the world class banks. Conversely, the purpose of this study is targeted to investigate the influence of customer and internal marketing as prerequisite for employees’ job satisfaction. The research design was descriptive correlational study and data were collected through survey questionnaires. The study utilized simple random sampling methods to select 384 employees in Nigeria banking industry from 12 selected commercial banks in Lagos state Nigeria, with the response rate of 94% from the total population of employees who are currently working in the 12 selected commercial banks in Lagos. 364 respondents were successfully returned and completed out of 384 who participated in the study comprising of 183 (50.3%) males and 181 (49.7%) females. The findings showed that employee’s job satisfaction is high and also the descriptive statistics revealed that internal marketing practices are the most reliable mechanism through which the objectives of Nigeria banking industry can be achieved. The study has emphasized strongly on the concepts of internal marketing and employees’ customers’ orientation as the crucial components through which employees’ job satisfaction can be determined in organization, especially in a financial institution such as banking industry in Nigeria. Nigeria banking industry is expected to re-strategize and rethink their attitude in order to attain competence and adequacy in the banking sector. Lack of employees’ customer orientation and the practices of internal marketing in Nigerian banking industry is seen as a catastrophic attempt. Thus, job satisfaction of employees is seen as crucial. Therefore, it is believed that these are the instrument of change and a reliable factor that is capable of transformation towards employees, and ability to operate constructively as to reciprocate to the concept of job satisfaction in Nigeria banking industry.